Over-nutrition in children and influence of parental attributes (Journal of Kathmandu Medical College, 2018)
Over-nutrition has presented itself as a significant public health issue in the past few decades. Its burden is increasing not only in developed countries, but also in developing countries. The objective of this review was to explore global and national burden of over-nutrition, its prevalence among children, and identification of the risk factors. It focused on assessing behavioral and socio-demographic attributes of parents that may influence obesity/overweight in children. For writing the literature review, national and international reports on over-nutrition, along with many journal articles on the related topic were reviewed. It showed that the burden of overweight/obesity has increased notably in the last three decades and is increasing more rapidly in developing countries. Moreover, it illustrated that its prevalence is high and has an increasing trend among children. Further more, the review also highlighted that parental attributes have an important influence on children’s nutritional status. Thus given the important role that parents play in the nutrition of children, parents need to be a focus of the strategies to control the growing problem of over-nutrition among children.